What Do the Panama Papers Teach Us About the Administrative Law of Corporate Governance Reform in Hong Kong? - Bryane Michael; Say-Hak Goo (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
A complex business environment calls for a flexible administrative law for the agencies that oversee corporations. No where illustrates this maxim better than Hong Kong, and its need to reform corporate regulations after the Panama Papers revelations. We describe how only a `non-administrative' administrative law can best cope with the challenges facing the regulation of corporate governance. Such a flexible, results-oriented approach to administrative law develops new principles and tests, rather than gives civil servants instructions. Such an approach to corporate governance can facilitate the assessment of company governance, corporate disclosure, the self-regulation of professional groups like lawyers and accountants, as well as ensure corporations engage in `legitimate economic purposes.' We engage with the literature, showing why such a flexible approach to administrative rulemaking would more likely reduce some of the government regulation and oversight problems exposed by the Panama Papers than previous approaches toward drafting and implementing administrative law (at least in this area).
Keywords: 330; Hong Kong corporate governance; non-administrative administrative law; presumption of disclosure; legitimate economic purposes